2013
DOI: 10.4236/ajps.2013.410243
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carbohydrates, Mineral Nutrients and Plant Hormones in Alternate Bearing of Black Pepper (<i>Piper nigrum</i> L.)

Abstract: Alternate bearing habit, a common phenomenon prevalent in some of the fruit trees is observed in black pepper variety Panniyur-1 also. In this study, an attempt was made to investigate the role of carbohydrates, mineral nutrients and plant hormones (IAA and zeatin riboside) in alternate bearing in Panniyur-1 variety. The experiment was conducted for three consecutive years at Murugarajendra estate, Madikeri, Karnataka, India (12.42˚ N, 75.73˚ E). Carbohydrate, mineral nutrient and plant hormone (IAA and zeatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…Tanaman lada termasuk tanaman yang rakus hara, artinya untuk dapat tumbuh dan menghasilkan dengan baik diperlukan unsur hara yang sangat banyak. Menurut Krishnamurthy et al (2013), pada varietas lada Panniyur-1, produksi dikendalikan oleh cadangan karbohidrat dan ketersediaan nutrisi pada saat inisiasi primordial bunga. Cadangan karbohidrat yang dikombinasikan dengan hormon auksin dan sitokinin sampai batas tertentu dapat berperan dalam inisiasi bunga dan pengisian buah lada.…”
Section: Karakteristik Komponen Hasilunclassified
“…Tanaman lada termasuk tanaman yang rakus hara, artinya untuk dapat tumbuh dan menghasilkan dengan baik diperlukan unsur hara yang sangat banyak. Menurut Krishnamurthy et al (2013), pada varietas lada Panniyur-1, produksi dikendalikan oleh cadangan karbohidrat dan ketersediaan nutrisi pada saat inisiasi primordial bunga. Cadangan karbohidrat yang dikombinasikan dengan hormon auksin dan sitokinin sampai batas tertentu dapat berperan dalam inisiasi bunga dan pengisian buah lada.…”
Section: Karakteristik Komponen Hasilunclassified
“…Faktor-faktor lain yang berpengaruh adalah ketersediaan bibit unggul, perubahan iklim, serangan hama dan penyakit, harga yang rendah yang dapat mendorong petani mengganti pertanaman lada menjadi pertanaman lainnya (Karmawati et al, 2020;Krishnamurthy et al, 2011). Varietas cuaca dan keadaan unsur hara dalam tanaman akan menyebabkan terjadinya fluktuasi produksi lada yang disebut sebagai "alternate bearing" yaitu produksi lada yang lebat akan diikuti produksi kecil (Krishnamurthy et al, 2013).…”
Section: Pendahuluanunclassified
“…Lavee (2007) found that the main endogenous and environmental factors and their interactions lead to the alternate bearing in olive. Krishnamurthy et al (2013) studied the influence of carbohydrate, minerals and hormones (IAA and zeatin riboside) on alternate bearing in black pepper (Piper nigrum L). Nafeez et al (2013) reported sustainable yield can be obtained in mango by managing irregular bearing through foliar spray of urea.…”
Section: Introductionmentioning
confidence: 99%